Educação das relações étnico-raciais : escrevivências de estudantes negras(os) em um município marcado pela colonialidade ítalo-brasileira - Rosa, Joelma Couto (My University, 2025)
This research aims to promote a reflection on the implementation of Law 10.639/2003 and the Education of Ethnic-Racial Relations in the Municipal School System of Caxias do Sul, a municipality located in the Serra Gaúcha, as well as to problematize issues related to whiteness and white supremacy. The study was anchored in the Postgraduate Program in Education at the University of Caxias do Sul and in the Research Line: History and Philosophy of Education. It is qualitative research, constructed from the escrevivências - a concept coined by the writer Conceição Evaristo - of black adolescents, students in the 7th, 8th and 9th grade of Elementary School, aged between twelve and fifteen years old. In this sense, the study was conducted in a relationship of subjectivity between the researcher and her relationship with the theme, which is not just a theme. It is life. The lives of people in movement. This approach seeks to give voice to the experiences, stories, memories and subjectivities of the participants, promoting a deep connection between writing, identity and the struggle for recognition. In this way, writing in the form of a letter creates an intimate, direct and affective connection between the writer and the reader, as it allows for confidences, personal reflections and dialogues with the other person and with oneself. The study was conducted at a school in the Caxias do Sul Municipal Education Network, located very close to "Burgo", a community with a significant black presence in this municipality strongly marked by Italian-Brazilian coloniality. The investigation, carried out through written messages, that is, letters with varied written productions, exchanged between the researcher and the students, had as its central objective to analyze and understand how the Education of Ethnic-Racial Relations is lived and experienced by them and addressed by administrators and teachers, in a context of Italian-Brazilian coloniality, in which there is a predominance of whiteness in teaching - which will be referred to in this study as teaching whiteness. The debate was carried out in a municipal school, located very close to a community with a significant black presence in this municipality strongly marked by Italian-Brazilian coloniality. The study of race relations is not new in national and international academic research, which is not reflected in the context of Caxias do Sul, where the first studies on this topic are still timid, and blackness always appears as the central element. Likewise, through this study, I present the possibility of analyzing the racialization of white people in contexts of Italian-Brazilian coloniality. This term is situated within the logic of the expansion of European colonialism over the rest of the world, which reinforces the erroneous and misguided idea of the superiority of Europeans in relation to other exploited peoples. By addressing whiteness, I seek to provoke a movement to break with the idea that ethnic-racial relations are only about black or indigenous people. Thus, considering that the concept of whiteness is directly linked to a place of symbolic, subjective and objective privileges, which contribute to the social construction and reproduction of racism, this study contributes to the process of promoting a more equitable and anti-racist education, in an attempt to understand how the concept of whiteness and white supremacy are hidden in the school curriculum, from the perspective of black students. The results obtained through the writings reveal this agency of white supremacy in the context of education, as most of them brought many complaints about the occurrence of racism in the school space and that it goes unnoticed by white teachers. However, some revealed attitudes of empowerment of the students and there were those who presented important self-transformative movements in relation to the racial identity of these adolescents. Given this perception, the writings that arrived through letters were organized into these three categories: complaints, empowerment and self-transformation, as an analysis strategy. The results of the research are also presented in the form of letters, according to this categorization, in which the researcher - an adult black woman - writes to her inner child. Thus, this is research that intends to destabilize truths imposed by whiteness, which silence, make invisible or make visible in a perverse way the history, culture and knowledge of non-white subjects. [resumo fornecido pelo autor]
A presente pesquisa busca promover uma reflexão acerca da implementação da Lei 10.639/2003 e da Educação das Relações Étnico-Raciais na Rede Municipal de Ensino de Caxias do Sul, município localizado na Serra Gaúcha, bem como problematizar questões relativas à branquitude e à supremacia branca. O estudo foi ancorado no Programa de Pós-graduação em Educação da Universidade de Caxias do Sul e na Linha de Pesquisa: História e Filosofia da Educação. É uma pesquisa qualitativa, construída a partir das escrevivências - conceito cunhado pela escritora Conceição Evaristo - da pesquisadora, uma professora negra, e de 32 adolescentes negras(os), estudantes de 7º, 8º e 9º ano do Ensino Fundamental, com faixa etária compreendida entre doze e quinze anos de idade. Nesse sentido, o estudo se fez numa relação de subjetivação da pesquisadora e sua relação com o tema, que não é apenas um tema. É vida. Vida de pessoas em movimento. Essa abordagem busca dar voz às vivências, histórias, memórias e subjetividades das(os) participantes, promovendo uma conexão profunda entre a escrita, a identidade e a luta por reconhecimento. Dessa maneira, as escrevivências no formato de carta criam uma conexão íntima, direta e afetiva entre quem escreve e quem lê, pois permite confidências, reflexões pessoais e diálogos com a(o) outra(o) e consigo mesma(o). O estudo foi realizado em uma escola da Rede Municipal de Ensino de Caxias do Sul, situada muito próximo ao "Burgo", uma comunidade com expressiva presença negra neste município fortemente marcado pela colonialidade ítalo-brasileira. A investigação realizada por meio das escrevivências, aqui mobilizadas através de cartas com produções escritas variadas, trocadas entre a pesquisadora e as(os) estudantes, teve como objetivo central analisar e compreender como a Educação das Relações Étnico-Raciais é vivida e experienciada por elas(es) e abordada por gestoras(es) e professoras(es), num contexto de colonialidade ítalo-brasileira, em que há uma predominância da branquitude na docência - o que será denominado nesse estudo de branquitude docente. O debate acerca das relações raciais não é recente em pesquisas acadêmicas nacionais e internacionais, o que não se reflete no contexto de Caxias do Sul em que os primeiros estudos acerca desta temática ainda são tímidos e a negritude sempre aparece como o elemento central. Por meio deste estudo, apresento a possibilidade de analisar a racialização das pessoas brancas em contextos de colonialidade ítalo-brasileira. Esse termo situa-se dentro da lógica da expansão do colonialismo europeu sobre o restante do mundo, o que fortalece a ideia errônea e equivocada de superioridade do europeu em relação aos demais povos explorados. Ao abordar a branquitude, busco provocar um movimento de romper com a ideia de que relações étnico-raciais se trata apenas de pessoas negras ou indígenas. Desta forma, considerando que, o conceito de branquitude está diretamente ligado a um lugar de privilégios simbólicos, subjetivos e objetivos, que colaboram para a construção social e reprodução do racismo, este estudo contribui com o processo de promoção de uma educação mais equânime e antirracista, na tentativa de apreender como o conceito de branquitude e de supremacia branca se escondem no currículo escolar, pela perspectiva das(os) estudantes negras(os). Os resultados obtidos através das escrevivências, escancaram essa agência da supremacia branca no âmbito da educação, pois a maioria delas trouxeram muitas denúncias sobre a ocorrência do racismo no espaço da escola e que passa despercebido pela branquitude docente. Algumas cartas revelaram atitudes de empoderamento das(os) estudantes, outras apresentaram importantes movimentos autotransformativos em relação à identidade racial dessas(es) adolescentes. Diante dessa percepção, as escrevivências que chegaram pelas cartas foram organizadas em três categorias: denúncias, empoderamento e autotransformação, como uma estratégia de análise. O resultado da pesquisa também é apresentado em formato de cartas, de acordo com essa categorização, em que a pesquisadora - uma mulher negra adulta - escreve para a sua criança interior. Assim, essa é uma pesquisa que intenciona desestabilizar verdades impostas pela branquitude que silenciam, invisibilizam ou visibilizam de maneira perversa a história, a cultura e os saberes de sujeitos não-brancos. [resumo fornecido pelo autor]
Keywords: Educação - Caxias do Sul (RS); Educação - Caxias do Sul (RS) - Legislação; Identidade social - Análise do discurso; Negros - Caxias do Sul (RS) - Estudantes; Relações étnicas - Estudo e ensino; Relações raciais - Estudo dirigido; Education - Caxias do Sul (Brazil); Education - Caxias do Sul (Brazil) - Legislation; Group identity - Discourse analysis; Blacks - Caxias do Sul (Brazil) - Students; Ethnic relations - Study and teaching; Race relations - Study and teaching